PERTUSSIS IN CHILDREN – CLINICAL AND EPIDEMIOLOGICAL CHARACTERISTICS IN THE SAMARA REGION - E. S. Gasilina; S. M. Kitajchik; I. A. Gorelova; N. P. Kabanova; O. A. Fedoseeva; I. Yu. Bogoyavlenskaya; O. M. Revtovich; N. M. Bochkareva; G. V. Santalova; A. A. Frank (Журнал инфектологии, 2018)
Objective: to study the features of the clinical and epidemiological characteristics of whooping cough in children in the Samara region.Materials and methods: 389 cases of pertussis in the Samara region for 2015–2016 were analyzed.Results: it is shown that in spite of 95–98% vaccination coverage, in recent years there has been an increase in the incidence of whooping cough. Seasonality of morbidity remains. Among the children observed, the youngest children were not vaccinated against pertussis. The clinical picture of the disease remains typical with the classic course of catarrhal and spasmodic periods. Moderately severe forms of the disease predominate. Complications were noted mainly in unvaccinated children of the first year of life. The most frequent complications were pneumonia and apnea. There is a hypodiagnosis of pertussis in outpatient conditions. Infection often occurs under the mask of ARVI, while the sensitivity of the bacteriological method of diagnosis is zero. Of the methods for confirming the diagnosis, the most reliable is ELISA and PCR.Conclusion: these epidemiological and clinical features of pertussis current testify to the need to further improve methods of early diagnosis, especially express methods, etiopathagenetic treatment, specific prevention, antiepidemic measures in the foci of infection.